Respuesta :

Answer:

y - 1 = 3/2(x - 6)

Step-by-step explanation:

First, we need to find the slope of the given equation. Without a graph, the easiest way to do this is by isolating y.

2x + 3y = 18

3y = -2x + 18        (Subtract 2x from both sides)

y = -2/3x + 6        (Divide both sides by 3)

The slope is -2/3. Perpendicular lines have opposite reciprocal slopes, so a line perpendicular to this one would need to have a slope of 3/2. We're given a point for this line, so we can write the equation for it in point-slope form.

Point-Slope Form: [tex]y - y_{1}=m (x-x_{1})[/tex]

y - 1 = 3/2(x - 6)

If necessary, this can also be written in slope-intercept form by solving for y.

ACCESS MORE